Advanced Selectively Gas Permeable Anode Flow Field Design for Removal of Carbon Dioxide in a Direct Formic Acid Fuel Cell. Issue 1 (16th December 2016) - Saeed, S.; Pistono, A.; Cisco, J.; Burke, C. S.; Clement, J. T.; Mench, M.; Rice, C.
Abstract: Direct formic acid fuel cells (DFAFCs) are electrochemical energy conversion devices well suited to power portable electronics, if researchers can harness their high theoretical efficiencies and address durability issues. To improve DFAFC efficiency, the mass transport of formic acid to the anode catalyst layer must be improved. Conventional serpentine anode flow field designs limit CO2 product removal through a single flow field channel hindered by two‐phase flow. Presented herein is an advanced electrically conductive, selectively gas permeable anode flow field (SGPFF) design that allows for efficient removal of CO2 perpendicular to the active area near the location where it is formed in the catalyst layer. The anode plate design consists of two mating flow fields separated by semi‐permeable separator to allow diffusive transport of CO2 . Herein, performance differences between a conventional liquid‐fed flow field and an advanced SGPFF design are examined. Polarization curves revealed a 10% increase in performance of the SGPFF with confirmation of CO2 removal within the gaseous side. A potential hold test at 0.3 V showed that the SGPFF sustained power generation for 9.5 times longer than that of the conventional anode flow field design in a dead‐ended configuration, demonstrating the fixture's potential for sustained power generation.